Carbohydrates digestibility and faecal microbiota composition in rats fed diets based on raw or fermented Vigna unguiculata seed meal as the only protein source. (October 2022) - Kapravelou, Garyfallia; Fernández-Fígares, Ignacio; Ruiz, Raquel; Jesús Peinado, M.; Martin-Pedrosa, Mercedes; Porres, Jesús M.; Rubio, Luis A.
Highlights: Digestibility of NSPs differed between casein and Vigna diets Vigna processing (fermentation and autoclaving) reduced the amounts of α-galactosides NSP digestibility clustered with bacterial groups associated to casein diet Oligosaccharides digestibility clustered with bacterial groups associated to cowpea diets Dietary inclusion of V. unguiculata induced a healthier intestinal microbiota pattern ABSTRACT: Cowpea (Vigna unguiculata) value as a functional food is still quite underexplored. Weaned Wistar albino rats were fed one of four experimental equilibrated diets based on casein or cowpea meal as the only protein sources. RT-qPCR analysis showed that the replacement of casein for raw or treated cowpea meal lowered Escherichia/Shigella faecal counts and increased Lactobacilli, Bifidobacteria, Bacteroides, Clostridium leptum/Ruminococcus, and Faecalibacerium prausnitzii log10 counts. Sequencing (Illumina) analysis confirmed these results and revealed that rats fed the cowpea-based diets presented higher proportions of potentially beneficial bacterial groups. Non-starch polysaccharides digestibility was associated with bacterial groups related with the control diet, while oligosaccharides digestibility was associated with cowpea diets. In conclusion, the inclusion of Vigna unguiculata in diets for rats, particularly in the untreated form, induced a healthier intestinal microbiota composition, which was mainly linked to the fermentation of oligosaccharides of the raffinose family.